(untitled) (Observatorio Económico, 2012)
A couple of months ago, the press carried a controversy between Senator Girardi and former Minister Velasco that brought the old issue of political clientelism back into the spotlight. Velasco accused the senator of demanding, before he took office, that members of the senator’s party be appointed to the Ministry of Finance and, upon his refusal, of threatening to boycott his bills in Congress. In other words, he was blackmailed. In turn, the senator charged that the former minister had lobbied on behalf of Endesa so that the Dirección de Aguas (Chile’s water rights authority) would grant water rights to that company. Continue reading...